PENINGKATAN PENYELENGGARAAN PEMERINTAHAN YANG BERSIH dan BEBAS KKN DAN INDIKATOR-INDIKATOR HASILNYA - Fefta Wijaya, Andy (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2012)
This paper presents this new perspective of public management (NPM) and governance in administrative sciences and explains the differences between of them. NPM risk leaving the public service function for the poor and marginalized, therefore improving governance perspective NPM movement's weakness. New Public Management Paradigm with no accountability (accountability) would risk leaving the public interest. Accountability as a fundamental pillar of good governance paradigm can improve the weaknesses found in the paradigm previously thought. A major component to the success of public accountability is a system of information transparency. Transparency of information is authorized to be used for public sector performance evaluation measures and for evaluating public sector executive accountability for all decisions and actions, ie to what extent the results / outcomes and impacts resulting from beneficial to the public.